Utilização da macroalga Gracilaria birdiae no desenvolvimento de produtos alimentícios - Vasconcelos, Bárbara Monique de Freitas (2015)
The objective was used the seaweed Gracilaria birdiae on development of two food products, seeking to increase the protein percentage and consumption of seaweed. The G. birdiae was dried in solar dryer and mechanical oven in order to find what the best process that ensures its nutritional value. From the G. birdiae dehydrated were produced the crackers with seaweed and the shrimp ball breaded with seaweed. Were carried out proximal composition, or microbiological analysis and sensory analysis of both products. The cracker were packaged under modified atmosphere (100% N2) and stored for 180 days at room temperature to evaluate the shelf life. The shrimp ball was packed in modified atmosphere and stored under refrigeration (4 ° C) for 15 days for evaluation shelf life. The results showed that drying in an oven (60ºC) that was granted better nutritional quality, the protein percentage was noted (14%). Microbiological analysis of seaweed in nature was within the limits of the law, and dehydrated seaweed was not detected the presence of microorganisms, confirming the hygienic and health care during processing. The protein percentage of developed products was the most prominent (15% for cracker 16% for shrimp ball). The microbiological evaluation of the products demonstrates growth of mesophilic (shrimp ball with seaweed), molds and yeasts (cracker with seaweed), but below the limit established by law. The developed products have been well accepted in sensory analysis. The results of the study showed that the shelf life of the product developed were stable physical-chemical and microbiological throughout the storage period. The modified atmosphere ATM 3 (80% CO2 | 20% N2 | 0% O2) was the most efficient to keep the physical, chemical and microbiological standards cookie. The seaweed G. birdiae presented high protein percentage, excellent sensory profile when included in food products, and can be considered as promising ingredient in the food industry